Mineralogía de las arcillas, limos y arenas en seis suelos de Panamá - Martini, J. A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
A mineral characterization with X-ray diffraction was performed on the clays, silts and sands of six surface soils from Panama belonging to five great soil groups, namely, latosol, planosol, alluvial, alluvio-volcanic and andosol. All soils came from the Pacific slopes of Panama with a definite dry season of three to five months. The mineralogical composition was quite variable, depending on the soil and soil fraction. The secondary minerals, kaolinite, montmorillonite and vermiculite, in that order, were predominant in the clay fractions. The silts particularly the finer fraction, had some vermiculite, kaolinite, and traces of montmorillonite. The clay mineral content decreased with increasing particle size, except for vermiculite which increased up to the fine silts. Kaolinite was predominant in the latosol and planosol; however, the cation exchange capacity of the latosol was higher than expected due to the presence of allophane and organic matter. Kaolinite, vermiculite and montmorillonite occurred in that order in the alluvial soils. The presence of 2.1 lattice clays justified the high cation exchange capacity and possibly the high organic matter levels. Amorphous materials, some kaolinite and vermiculite and traces of montmorillonite were present the soils derived on volcanic ashes. The predominance of kaolinite suggests that allophane change directly to this mineral or that vermiculite and particularly montmorillonite are transitory stages or limited stability and duration. The high content of allophane was associated with a high cation exchange capacity, high organic matter levels and low pH values. The high contents of organic matter are said to represent an intrazonality due to the high levels of allophane which slows down organic matter decomposition. The presence of secondary minerals in the silts indicates that this fraction contributes significantly to the cation exchange capacity of the soils. The contents of primary minerals in decreasing order were, quartz, feldspars and amphiboles. These minerals were more abundant in the sands and least in the clays. The feldspar levels correlated well with the quantities of structural K present. Feldspars were highest in andosols and lowest in latosol. The quartz content followed an inverse relation to the feldspars, being highest in the latosols and lowest in the andosols.